DNA sequence of the mitochondrial hypervariable region II from the Neandertal type specimen - Krings, Matthias (The National Academy of Sciences, 1999)
The DNA sequence of the second hypervariable region of the mitochondrial control region of the Neandertal type specimen, found in 1856 in central Europe, has been determined from 92 clones derived from eight overlapping amplifications performed from four independent extracts. When the reconstructed sequence is analyzed together with the previously determined DNA sequence from the first hypervariable region, the Neandertal mtDNA is found to fall outside a phylogenetic tree relating the mtDNAs of contemporary humans. The date of divergence between the mtDNAs of the Neandertal and contemporary humans is estimated to 465,000 years before the present, with confidence limits of 317,000 and 741,000 years. Taken together, the results support the concept that the Neandertal mtDNA evolved separately from that of modern humans for a substantial amount of time and lends no support to the idea that they contributed mtDNA to contemporary modern humans.